KEBEBASAN PERS DALAM PERSPEKTIF PERADILAN PIDANA - Ariyanti, Vivi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Freedom of the press in the perspective of the criminal justice is the use of the provisions of the Criminal Code; itis not limitation or restraint on freedom of the press, because the provision was only a tool that is used for the testing of limitativeconduct a press working process. Testing can be done by using specific parameters as stipulated in the convention on thefreedom of information, such as the press can not be prosecuted in criminal law except when to do positive things likecontempt, sedition, blasphemy, pornography, a lie news, disturb national security and public order and statements thatimpede the fair administration of justice. Therefore, in press freedom, presenting news must be based on features newsjournalist code of ethics that exist